Characteristics of Chitosan from White Leg Shrimp Shells Extracted Using Different Temperature and Time of the Deasetilation Process - Beni Setha; Fitriani Rumata; Bernita br.Silaban (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Chitosan is a white amorphous solid chitin, and of high biological and mechanical characteristics.Chitosan production is divided into two stages. First is chitin isolation (deproteination, demineralization,and depigmentation), and second is deacetylation of chitin to chitosan. This research was aimed to determinethe characteristic of chitosan isolated from the shells of the white leg shrimp using different temperatureand time in the deasetilation process. The FTIR test results showed that the chitin group was partiallybroken into chitosan in every treatment. The highest content of chitosan was obtained at the temperaturetreatment of 100oC for 2 hours, while the highest degree of deacetylation, viscosity, and molecular weightwere observed at the temperature treatment of 120oC for 3 hours. The sample were not soluble in aquades,methanol, or ethanol indicating the samples were chitosan.